Special Issue on Standalone Renewable Energy System: Modeling and Controlling - Rodolfo Dufo-López; José L. Bernal-Agustín (Applied Sciences, 2020)
Standalone (off-grid) renewable energy systems supply electricity in places where there is no access to a standard electrical grid [...]